Factors Influencing Consumers’ Attitudes towards Digital Communications within the South African Banking Industry - Sharp, Kirsty-Lee; Lues, Heleneze; Klonaridis, Rita; Van Deventer, Marko; Müller, Re-an; Redda, Ephrem (International Review of Management and Marketing, 2024)
The purpose of this study was to explore the factors that influence consumers’ attitudes towards digital communications within the South African banking industry by validating a six-factor model and determining the influence of entertainment, invasiveness, personalisation, informativeness and credibility of banks’ digital communication on consumers’ attitudes towards the digital communication of banks. The identified respondents for this study constituted 500 South African adults aged 18 years and older. This sample size was in line with the requirements for structural equation modelling (SEM), which was the primary method used to analyse the captured data. When collecting the data, the services of a market research company were employed. A computer-administered questionnaire, including a cover letter outlining the purpose of the study, as well as a section that requested demographic information was used. As per the findings of this study, the model presents acceptable reliability and adequate model fit. Consequently, the hypothesised model includes six factors, namely entertainment, informativeness, credibility, personalisation, invasiveness and attitudes. The model and recommendations in this study may assist banks in their efforts to continuously assess and improve how they create, manage and enhance their digital communications.